2010
DOI: 10.1096/fj.09-151506
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Na+inhibits the open probability of the epithelial sodium channel in the kidney by enhancing apical P2Y2‐receptor tone

Abstract: Apical release of ATP and UTP can activate P2Y(2) receptors in the aldosterone-sensitive distal nephron (ASDN) and inhibit the open probability (P(o)) of the epithelial sodium channel (ENaC). Little is known, however, about the regulation and physiological relevance of this system. Patch-clamp studies in freshly isolated ASDN provide evidence that increased dietary Na(+) intake in wild-type mice lowers ENaC P(o), consistent with a contribution to Na(+) homeostasis, and is associated with increased urinary conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
170
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(186 citation statements)
references
References 38 publications
15
170
1
Order By: Relevance
“…Resting ENaC activity was greater in P2Y 2 −/− receptor mice than controls suggesting that local ATP may be involved in the regulation of basal ENaC activity in the murine collecting duct [289,290]. Additional studies from the same laboratory demonstrated that ENaC downregulation in response to sodium restriction was lost in the P2Y 2 null mice, suggesting a role for the receptor in the renal response to altered sodium intake [291]. Despite this, the hypertension was not saltsensitive, suggesting that these renal changes are compensated for elsewhere.…”
Section: Sodium Transportmentioning
confidence: 94%
“…Resting ENaC activity was greater in P2Y 2 −/− receptor mice than controls suggesting that local ATP may be involved in the regulation of basal ENaC activity in the murine collecting duct [289,290]. Additional studies from the same laboratory demonstrated that ENaC downregulation in response to sodium restriction was lost in the P2Y 2 null mice, suggesting a role for the receptor in the renal response to altered sodium intake [291]. Despite this, the hypertension was not saltsensitive, suggesting that these renal changes are compensated for elsewhere.…”
Section: Sodium Transportmentioning
confidence: 94%
“…Animals were maintained on standard rodent regimen (PURINA 5001) and had free access to tap water. For some experiments, mice were injected with deoxycorticosterone acetate (DOCA) for 3 consecutive days (2.4 mg/injection per animal) prior to the experimentation as we have done previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue Isolation-The procedure for isolation of the ASDNs containing the connecting tubule and the CCD suitable for electrophysiology and Ca 2ϩ -imaging has been described previously (27)(28)(29). Briefly, mice were sacrificed by CO 2 administration followed by cervical dislocation; the kidneys were removed immediately.…”
Section: Methodsmentioning
confidence: 99%
“…1 Nucleotide metabolism in a nutshell. UTP is identically released and degraded and has been found in both gastrointestinal [32], respiratory [33][34][35][36], and renal epithelium [37][38][39]. Since the P2Y2 receptor has equal affinity for both ATP and UTP, both these mediators can activate the receptor.…”
Section: P2rmentioning
confidence: 99%
“…The most studied mechanism of ENaC activity involves membrane trafficking of the protein [42], but a recent study of the P2Y2 receptor-mediated inhibitory response suggests that purinergic control is conveyed by changes in channel open probability rather than plasma membrane levels of the protein [39]. The way that P2Y2 receptor activation influences ENaC activity has previously been attributed to PLC activation and PIP2 depletion [43].…”
Section: P2rmentioning
confidence: 99%